ANALISIS TINGKAT EFISIENSI SELURUH BRANCH OFFICE CREDIT UNION KELING KUMANG DI KALIMANTAN BARAT DENGAN METODE DATA ENVELOPMENT ANALYSIS - admin, SUJIMAN B2052162012 (Jurnal Ekonomi Daerah (JEDA), 2019)
The difference in the amount of output produced, especially in the income variable in each branch office incorporated in the 6 office areas of CU Keling Keling is one of the basic or reasons that the writer wants to disclose as research material. This study aims to analyze the efficiency of all branch offices at Credit Union Keling Kumang and to determine the branch office of CU Keling Kumang which can be used as a benchmarking for other branch offices. This study uses a non-parametric Data Envelopment Analysis approach. Data used during the 2017 period which includes 61 branch offices of the Credit Union Keling Kumang in West Kalimantan. The results of the research study showed that the technical efficiency performance of Credit Union Keling Kumang contained 3 branch offices which reached a maximum efficiency point of 100%, namely Branch office Ng. Belitang, Batu Buil Branch Office and Sayan Branch Office while 58 other branch offices are still inefficiencies with an efficiency score of between 25.68% s.d. 94.44%. Â Keywords: Efficiency, Third Parties Funds, Price of Labor, Interest Cost, Workforce Total, Credit Total, Income Total